1991
DOI: 10.5035/nishiseisai.39.1519
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Prostaglandin E1 on Patients of Lumbar Canal Stenosis.

Abstract: We treated 10 patients of lumbar spinal canal stenosis with intravenous drip of Prostaglandin E1. Doses were 120pg/day or 60 ,ug/day during a week. Four cases were very good and 4 cases were good on satisfaction of patients. The test of spinal evoked potential was done on 7 cases. We recorded at rest and after load of gait, and compared the prolongation of latency and the decline of amplitude between pre and post-treatment. After treatment, the prolongation of latency by load of gait decreased in comparison wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…A literature search found 10 studies that reported clinical outcomes of PGE 1 treatment for LSCS (Table ) . Takakura et al .…”
Section: Clinical Outcomes Of Pge1 Treatment For Lscsmentioning
confidence: 99%
“…A literature search found 10 studies that reported clinical outcomes of PGE 1 treatment for LSCS (Table ) . Takakura et al .…”
Section: Clinical Outcomes Of Pge1 Treatment For Lscsmentioning
confidence: 99%